PENGEMBANGAN PERMAINAN MAKE A MATCH BERBASIS KOMPUTER SEBAGAI MEDIA PENGAYAAN - Rendy Putra Pratama; Rochmawati Rochmawati (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2020)
Learning media is believed to be one of the important parts of the learning process, especially computer-based media. This study aims to develop a computer game-based media Make a Match and to analyze its feasibility as a media enrichment. This study provided a type of educational Research and Development (RD) by referring to the model of development ADDIE (Analysis, Design, Development, Implementation, and Evaluation). The result of validations by material experts, linguists, and media experts showed thatthe average worthiness of assessment was 86,27%. The average percentage revealed the number of 90,1% in the material aspect, 81,4% in the linguistics aspect, and 86,7% in the media aspect. Therefore, this computer based-game is very decent to be used as amedia enrichment for students.